2014
DOI: 10.1186/s40560-014-0052-5
|View full text |Cite
|
Sign up to set email alerts
|

Oxygenation improves during the first 8 h of extended-duration prone positioning in patients with respiratory failure: a retrospective study

Abstract: BackgroundA recent multicenter trial demonstrated decreased mortality when patients with acute respiratory distress syndrome were treated with prone positioning (PP). However, the optimal duration of this treatment has not been established.MethodsFrom May 2010 to August 2013, 15 patients with respiratory failure underwent extended-duration prone positioning (more than 40 h) in the medical-surgical intensive care unit of a university hospital. The records of each patient were retrospectively investigated to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 13 publications
0
6
0
1
Order By: Relevance
“…We chose different V T between tested PEEP levels to limit lung overdistension and barotrauma during high PEEP while also avoiding lethal hypoxemia during low PEEP. Finally, ventilator settings and body positions were applied in-scanner for relatively short intervals: longer wait times (hours) would likely have enhanced the gas exchange effects of prone positioning (43, 44) but would have been impractical. However, serial CT scans confirmed that inflation distribution was not substantially altered while waiting for up to 1 hour in the prone position ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…We chose different V T between tested PEEP levels to limit lung overdistension and barotrauma during high PEEP while also avoiding lethal hypoxemia during low PEEP. Finally, ventilator settings and body positions were applied in-scanner for relatively short intervals: longer wait times (hours) would likely have enhanced the gas exchange effects of prone positioning (43, 44) but would have been impractical. However, serial CT scans confirmed that inflation distribution was not substantially altered while waiting for up to 1 hour in the prone position ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…According to our previous experience, we have applied prone ventilation for a longer duration than that stated in the abovementioned guideline, with a maximum duration of 43 h, which temporally cured his hypoxemia. 4,5 This allowed us to implement low tidal volume ventilation, bypassing the need for more invasive and resource-intensive procedures, such as extracorporeal membrane oxygenation (ECMO). Although prone ventilation is recommended for severe ARDS, published reports on the outcomes of prone ventilation used in COVID-19 patients are limited.…”
Section: Discussionmentioning
confidence: 99%
“…Here we reported a 79‐year‐old man with severe ARDS due to SARS‐CoV‐2 infection. According to our previous experience, we have applied prone ventilation for a longer duration than that stated in the abovementioned guideline, with a maximum duration of 43 h, which temporally cured his hypoxemia 4,5 . This allowed us to implement low tidal volume ventilation, bypassing the need for more invasive and resource‐intensive procedures, such as extracorporeal membrane oxygenation (ECMO).…”
Section: Discussionmentioning
confidence: 99%
“…found a similar result (cumulative incidence of 30%) with proning sessions of a median of 40 h. In this latter study, it should be noted that more than 10% of the sessions had a duration greater than 75 h [ 8 ]. Two observational retrospective studies have shown that the cumulative incidence of grade ≥ III PI associated with extended PP remained extremely low (between 0 and 2.5%) [ 8 , 30 ]. Finally, the occurrence of PI seems to be associated with the cumulated duration of PP and not with the duration of single sessions [ 8 , 31 ].…”
Section: Main Textmentioning
confidence: 99%